The Role of a Performance Coach on Athlete's Loyalty: A Case Study of Youth Soccer Players in San Diego and Orange County - Daniel O Jones; Ejiro Uriri Osiobe; Davi Sofyan (Indonesian Journal of Sport Management, 2022)
The definition of coach effectiveness is ambiguous, with several perceptions on creating an engaging learning environment. Thus, understanding why athletes remain with their respective organizations and recognizing the impact of their coach is essential to increasing retention rates. This study will review existing literature on coach effectiveness and the coach-athlete relationship impacting athlete engagement while mining primary data from elite academy soccer clubs in San Diego and Orange County. The results provide valuable information on athletes' and parents' decision(s) on what club they want to join based on the coaches' behaviors using a qualitative analysis approach. In addition, the results highlight correlations between the athletes' and parents' views of events. The study contributes' to providing practical information for youth sports organizations, who will be able to implement the recommendations of this study to enhance their coaches' education and create a positive coach-athlete experience.